The 1.5 Billion People Question : Food, Vouchers, or Cash Transfers? - Alderman, Harold (Washington, DC: World Bank, 2017)
Most of the people in low and middle-income countries covered by social protection receive assistance in the form of in-kind food. The origin of such support is rooted in countries’ historical pursuit of three interconnected objectives, namely attaining self-sufficiency in food, managing domestic food prices, and providing income support to the poor.